Histology, Fusion Status, and Outcome in Alveolar Rhabdomyosarcoma With Low‐Risk Clinical Features: A Report From the Children's Oncology Group. Issue 4 (12th January 2016) - Arnold, Michael A.; Anderson, James R.; Gastier‐Foster, Julie M.; Barr, Frederic G.; Skapek, Stephen X.; Hawkins, Douglas S.; Raney, R. Beverly; Parham, David M.; Teot, Lisa A.; Rudzinski, Erin R.; Walterhouse, David O.
Abstract : Background: Distinguishing alveolar rhabdomyosarcoma (ARMS) from embryonal rhabdomyosarcoma (ERMS) is of prognostic and therapeutic importance. Criteria for classifying these entities evolved significantly from 1995 to 2013. ARMS is associated with inferior outcome; therefore, patients with alveolar histology have generally been excluded from low‐risk therapy. However, patients with ARMS and low‐risk stage and group (Stage 1, Group I/II/orbit III; or Stage 2/3, Group I/II) were eligible for the Children's Oncology Group (COG) low‐risk rhabdomyosarcoma (RMS) study D9602 from 1997 to 1999. The characteristics and outcomes of these patients have not been previously reported, and the histology of these cases has not been reviewed using current criteria. Procedure: We re‐reviewed cases that were classified as ARMS on D9602 using current histologic criteria, determined PAX3/PAX7‐FOXO1 fusion status, and compared these data with outcome for this unique group of patients. Results: Thirty‐eight patients with ARMS were enrolled onto D9602. Only one‐third of cases with slides available for re‐review (11/33) remained classified as ARMS by current histologic criteria. Most cases were reclassified as ERMS (17/33, 51.5%). Cases that remained classified as ARMS were typically fusion‐positive (8/11, 73%), therefore current classification results in a similar rate of fusion‐positive ARMS for all clinical risk groups. In conjunction with data from COG intermediate‐risk treatment protocol D9803, our data demonstrate excellent outcomes for fusion‐negative ARMS with otherwise low‐risk clinical features. Conclusions: Patients with fusion‐positive RMS with low‐risk clinical features should be classified and treated as intermediate risk, while patients with fusion‐negative ARMS could be appropriately treated with reduced intensity therapy.